2021
DOI: 10.1177/15353702211004870
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of hydnocarpin D on T-cell acute lymphoblastic leukemia via induction of autophagy-dependent ferroptosis

Abstract: Hydnocarpin D (HD) is a bioactive flavonolignan compound that possesses promising anti-tumor activity, although the mechanism is not fully understood. Using T cell acute lymphoblastic leukemia (T-ALL) cell lines Jurkat and Molt-4 as model system, we found that HD suppressed T-ALL proliferation in vitro, via induction of cell cycle arrest and subsequent apoptosis. Furthermore, HD increased the LC3-II levels and the formation of autophagolysosome vacuoles, both of which are markers for autophagy. The inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…The above studies have shown that ALL is highly sensitive to ferroptosis ( 103 107 ), accompanied by excessive accumulation of ROS and increased lipid peroxidation level, which is consistent with the currently known classical pathway of ferroptosis. Overall, these studies offer novel insight into the molecular regulatory mechanisms of ferroptosis and may contribute to developing new therapeutic strategies to reactivate programmed cell death in ALL.…”
Section: Application Of Ferroptosis In Hematologic Malignanciessupporting
confidence: 85%
See 1 more Smart Citation
“…The above studies have shown that ALL is highly sensitive to ferroptosis ( 103 107 ), accompanied by excessive accumulation of ROS and increased lipid peroxidation level, which is consistent with the currently known classical pathway of ferroptosis. Overall, these studies offer novel insight into the molecular regulatory mechanisms of ferroptosis and may contribute to developing new therapeutic strategies to reactivate programmed cell death in ALL.…”
Section: Application Of Ferroptosis In Hematologic Malignanciessupporting
confidence: 85%
“…Hynocarpin D (HD) is a bioactive flavonoid lignin compound with good antitumor activity but insufficient understanding of its mechanism. Lou et al ( 103 ) found that in T-cell acute lymphoblastic leukemia (T-ALL) cell lines Jurkat and Molt-4, HD could inhibit the proliferation of T-ALL by inducing cell cycle arrest and subsequent apoptosis. In addition, HD could also increase LC3-II levels and the formation of autophagy lysosomal vacuoles, both of which are markers of autophagy.…”
Section: Application Of Ferroptosis In Hematologic Malignanciesmentioning
confidence: 99%
“…Typhaneoside, a flavonoid extracted from Pollen typhae , has also been reported to induce apoptosis and ferroptosis associated with ferritinophagy in AML cells [ 195 ]. Hydnocarpin D is another flavonoid demonstrated to induce apoptosis and ferroptosis through autophagy in ALL cells [ 196 ]. Perillaldehyde, the main component of Ammodaucus leucotrichus , downregulates GSH and GPX4 to induce ferroptosis in HL-60 cells and primary AML cells [ 197 ].…”
Section: Ferroptosis In Leukemiamentioning
confidence: 99%
“…Moreover, this cytotoxic autophagy caused ferroptosis, which was characterized by the accumulation of lipid ROS and a decrease in GSH and GPX4, and conversely, inhibition of autophagy hindered cell ferroptosis. [ 166 ] Soyauxinium chloride (SCHL) is a naturally occurring indole-quinazoline-type alkaloid. Some studies found that SCHL induced cytotoxicity of CCRF-CEM leukemia cells through caspase 3, 7, 8, and 9 activation, MMP alteration, and increased ROS generation, while the presence of Fer-1 (ferrostain-1) or DFA (deferoxamine; an iron-related death inhibitor) decreased SCHL cytotoxicity by 7.11- and 4.64-fold, respectively, indicating that SCHL is involved in ferroptosis.…”
Section: Recent Advances Of Ferroptosis In Almentioning
confidence: 99%